History. - Smoller, Laura Ackerman (Princeton legacy library., 2017)
Although astrology was viewed with suspicion by the medieval church, it became a major area of inquiry for the renowned cardinal and scholar Pierre d'Ailly, whose astrological and apocalyptic writings had a significant influence on Christopher Columbus. D'Ailly's writings on the stars, the focus of this book, clearly illustrate the complex relationships among astrology, science, and Christian thinking in the later Middle Ages. Through an examination of his letters, sermons, and philosophical, astrological, and theological treatises, Laura Ackerman Smoller reveals astrology's appeal as a scientific means to interpret history and prophecy, and not merely as a magical way to forecast and manipulate one's own fate. At the same time, she shows how d'Ailly dealt with delicate problems - such as free will and God's omnipotence - in elevating astrology to a compelling, but not always consistent, "natural theology."